Wavelet Rational Filters and Regularty Analysis (Journal of Computational Mathematics, 2000)
In this paper, we choose the trigonometric rational functions as wavelet filters and use them to derive various wavelets. Especially for a certain family of wavelets generated by the rational filters, the better smoothness results than Daubechies' are obtained.
Keywords: Wavelet; Filter; Rational filter; Regularity.